Psychiatric Sequelae of Flood-Induced Trauma: The Mediating Role of Social Isolation and Resilience in Older Adults - Tanveer Alam, Tayyab Arfeen, Muhammad Sheikh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Floods are one of the most frequent and destructive forms of natural disasters; they are calamitousfor vulnerable segments of populations, including older adults. Beyond physical destruction fromfloods, floods often lead to psychiatric sequelae, including post-traumatic stress disorder (PTSD), depression, and anxiety